Pendampingan Karang Taruna dalam Mitigasi Bencana Banjir Berbasis Aplikasi SADARI di Desa Dringu, Probolinggo - Nuriyanto; Miftahul Huda; Afrikatul Maulidiyah; Faishol Amrulloh; M. Imron Rosadi; M. Sulhan; Subchan Asy’ari; Nur Ajizah (BALE LITERASI, 2026)
Flood disasters frequently occur in Dringu Village, Probolinggo Regency, due to geographical conditions and the lack of an effective early warning system. This community service program aims to enhance the capacity of youth organizations (Karang Taruna) in flood mitigation through the utilization of the SADARI (Dringu Flood Early Warning System) application based on IoT technology. The beneficiaries of this program are members of Karang Taruna who serve as community-based disaster response teams. The method applied is a participatory empowerment approach, including problem identification, socialization, training, technology implementation, and mentoring and evaluation. The results indicate a significant increase in participants’ knowledge from 38% to 88%, as well as their ability to independently operate the SADARI application. The system is capable of providing early warnings 15–30 minutes before potential flooding, improving communication and coordination effectiveness among community members. Furthermore, the establishment of disaster response teams, development of standard operating procedures, and implementation of digital communication systems reflect strengthened institutional capacity. This program contributes to enhancing community preparedness and resilience through technology and has the potential to be replicated in other flood-prone areas.